Efficacy and safety of anlotinib plus programmed death-1 blockade versus anlotinib monotherapy as second or further-line treatment in advanced esophageal squamous cell carcinoma: A retrospective study - Liu, Ying; Ge, Qingqing; Xu, Shuning; Li, Ke; Liu, Ying (Frontiers in Oncology, 2022)
Background: Both anlotinib and programmed death-1 (PD-1) blockade have been approved for the second-line treatment of metastatic esophageal squamous cell carcinoma (ESCC). However, the combination of these two therapies has not been evaluated. This study investigated the efficacy and safety of anlotinib, a novel multitarget tyrosine kinase inhibitor targeting tumor angiogenesis, combined with PD-1 blockade as second or further-line treatment for advanced ESCC. Methods: Between January 2019 and February 2021, 98 advanced ESCC patients receiving anlotinib plus PD-1 blockade or anlotinib monotherapy as second or further-line treatment at Henan Cancer Hospital were retrospectively analyzed. Patients receiving anlotinib plus PD-1 blockade were grouped as cohort A (n=48), while those receiving anlotinib monotherapy were grouped as cohort B (n=50). The primary endpoint was progression-free survival (PFS). Secondary endpoints included the objective response rate (ORR), disease control rate (DCR) and toxicity. Furthermore, independent prognostic factors were identified by Cox regression analysis. A two-sided p-value of <0.05 was considered statistically significant. Results: Data was collected until May 1, 2021, with a median follow-up time of 9.30 months (8.23–10.37 months) in cohort A and 11.10 months (7.82–14.38 months) in cohort B. For patients with advanced ESCC, cohort A resulted in significantly longer PFS (5.40 vs. 3.00 months, P<0.001) and higher DCR (71.7% vs. 47.9%, P=0.019) than cohort B. The ORR indicated no significant difference between cohort A (23.9%) and cohort B (10.4%) (P=0.082). Adverse reactions were mainly grade 1/2 in the two groups. Compared with cohort B, a significantly higher rate of grade 1–2 hypothyroidism was observed in patients in cohort A (P= 0.034). Three patients (6.3%) developed grade 1/2 immune-related pneumonia. There was no significant difference in the incidence of grade 3-4 toxicities. Multivariable Cox regression analysis showed that the drug regimen (P＜0.001), Eastern Cooperative Oncology Group Performance Status (P=0.002), distant organ metastasis (P=0.008), and metastatic sites (P=0.032) were independent prognostic factors for PFS. Conclusions: Anlotinib plus PD-1 blockade showed promising anti-tumor activity and manageable toxicity as second or further-line treatment of advanced ESCC.